Evaluasi Kesesuaian Lahan untuk Tanaman Kopi Arabika (Coffea arabica L var Kartika Ateng ) Di Kecamatan Muara Kabupaten Tapanuli Utara - Bernart Jhensen Arihta Barus; Razali Razali; Gantar Sitanggang (Universitas Sumatera Utara, 2015)
This research aims to evaluate the land suitability of coffea (Coffea arabica L.) in Muara Subdistrict of North Tapanuli Utara. This research use survey method From the results of the overlay from the map of soil types, map of topography, and climate, retrieved 3 (three) units of land use map. SPL 1 has a land area of 796 hectares, SPL 2 has a land area of 243 hectares, and SPL 3 has a land area of 619 hectares.With the Matching method, then retrieved the land suitability class actual and potensial class for coffea (Coffea arabica L.) on each of the SPL. At SPL 1 and SPL 2 are actual land suitability class S3 (wa,nr) while the potential land suitability class is S3 (wa) and at SPL 3 is actual land suitability class S3 (wa,nr,eh) while the potential land suitability class is S3 (wa). Potention of land for Arabic coffea in Muara Subdistrict is 1658 Ha.Key words : land suitability, Arabic coffea, Muara Subdistrict